MARKETING CONFLICT AND SHARPENING ANTAGONISM: DOCUMENTING AND PRESERVING SOCIAL DIVISION IN THE FILM 3 HATI DUA DUNIA SATU CINTA - Hartanto, Denny Antyo; Murti, Ghanesya Hari; Sukmawati, Ni Luh Ayu; Astutiningsih, Irana (Capture : Jurnal Seni Media Rekam, 2023)
This research analyzes the 2010 film 3 Hati Dua Dunia Satu Cinta (3 Hearts Two Worlds One Love) amidst the social phenomenon indicating increased religious intolerance. Additionally, this study seeks to analyze social urban society's phenomenon and disparity through the film's narrative and characters. This research also seeks to understand the film's impact on urban society's heterogeneity from the spatial politics perspective. The study employed the qualitative method with narrative and discourse analysis approaches using Laclau-Mouffe's antagonistic framework. Data was collected by watching and directly analyzing the film and through relevant literature studies. The research results indicate that the film 3 Hati Dua Dunia Satu Cinta successfully utilized the social phenomenon as a marketing strategy, maintained disparity through its narrative and characters, resulted in subject dislocation towards a certain hegemonic identity, and influenced the heterogeneity of urban society from the perspective of spatial politics.